Supporting sporting integrity - the Council of Europe Database on Alleged Cases for Corruption in Sport (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The paper addresses the issue of corruption in sports, focusing on the Council of Europe’s initiative to establish a Database on Alleged Cases of Corruption in Sport. It illustrates the methodology used in constructing the Database and it shows some cases of corruption – occurred between 2016 and 2021 - included in the Database.
Keywords: corruption; sport; integrity; economic crime; organized crime